Physical Fitness in the Perspective of Islamic Education Philosophy (A Study of Teaching Physical Strength on Elementary Children) - Helfinasyam Helfinasyam; Salminawati Salminawati; Usiono Usiono (Universitas Pahlawan Tuanku Tambusai, 2023)
In Islam, physical education is no less important than other education. Because in the perspective of Islamic education, humans are created from two elements, physical (physical) and non-physical (spiritual). This study aims to analyze physical education for elementary age children. Research using library research or library research draws conclusions using content analysis methods, namely making conclusions (inferences) that can be imitated and with valid data, taking into account the context. This method is intended to analyze all discussions regarding the body in terms of the perspective of Islamic educational philosophy from several literature or manuscripts that examine this matter. The results of this study found that physical education is an important thing to give to children from an elementary age. As Rasulullah SAW. has taught friends to teach their children to ride, swim, and archery, all of which require physical strength. Thus, physical health will be a driving factor for elementary age children in strengthening non-physical or spiritual aspects. The conclusions of the study are (1) physical education is very much needed in the physical and motor development of elementary age children; (2) physical fitness is needed by children to increase their concentration in learning; and (3) physically and mentally healthy children have the opportunity to create critical and constructive learning products.